The Form and Extent of the Grenville Front Tectonic Zone in Proximity to Coniston, Ontario as Defined by Aeromagnetic and Paleomagnetic Studies of the Sudbury Olivine Diabase Dikes. - Manning, Susanne (My University, 1994)
Geophysical studies of the northwest trending Sudbury olivine diabase dikes, to the south of Coniston, Ontario establish a deformation zone, within the Southern province up to 10 km from the Grenville Front. Paleomagnetics reveal two directional groups within the dikes; those with a NRM direction of 300°/32° representing the primary magnetization of the dikes and those dikes with a Grenville overprint direction of 116°/56°. The deviation in direction of the two groups, in relation to previous studies (Palmer et al., 1977) is interpreted to be due to fault block movement. Aeromagnetics reveal extensive ductile and brittle deformation in the dikes as they approach the front. The general orientation of deformation is to the northeast.
Keywords: tectonic zone; aeromagnetic; paleomagnetic; geophysical; deformation zone